Will a once-weekly anticoagulant for the treatment and secondary prevention of thromboembolism improve adherence? - Cohen, Alexander T.; Maillardet, Louise; Yavin, Yshai (Thrombosis and Haemostasis, 2009)
Oral anticoagulation, most commonly with warfarin once daily, has long been the main form of long-term treatment and secondary prevention of thromboembolism. The efficacy of warfarin has been established in clinical trials, but problems with unstable anticoagulation with international normalized ratios (INRs) outside the recommended range due to incorrect dosing, drug and food interactions, and with adherence and persistence have been reported in practice. Poor adherence and persistence are serious problems because they result in out-of-range INRs. Many new thromboembolic events, such as strokes, occur when INRs are out-of-range or after warfarin discontinuation. Among the new anticoagulants currently being investigated, some offer the possibility of more stable anticoagulation and weekly administration. Less frequent dosing schedules generally improve adherence. In many cases, such as bisphosphonate treatment for osteoporosis, and the long-term treatment of depressive disorders or multiple sclerosis, adherence to, and persistence with, weekly dosing is improved compared with daily dosing, and most patients prefer weekly dosing. The advent of novel anticoagulants such as idraparinux with its long half-life offers hope for improved adherence with anticoagulation, and ultimately improved outcomes.
Keywords: Idraparinux; anticoagulant; thromboembolism; dose frequency; adherence